Multiple Periodic Solutions of a Nonautonomous Plant-Hare Model - Yongfei Gao; P. J. Y. Wong; Y. H. Xia; Xiaoqing Yuan (Abstract and Applied Analysis)
Based on Mawhin's coincidence degree theory, sufficient conditions are obtained for the existence of at least two positive periodic solutions for a plant-hare model with toxin-determined functional response (nonmonotone). Some new technique is used in this paper, because standard arguments in the literature are not applicable.